EFFECTS OF NEBIVOLOL VS NADOLOL ON GLUCOSE AND LIPID METABOLISM IN OVERWEIGHT HYPERTENSIVE PATIENTS. A OPEN RANDOMIZED CONTROLLED STUDY - E. R. Berngardt; A. O. Konrady; E. V. Smirnova; E. V. Shliahto (Российский кардиологический журнал, 2003)
Objective. The aim of the present study was to assess effects of treatment of overweight hypertensive patients with vasodilatating and non-vasodilatating beta-blockers on glucose and lipid metabolism.Patients and methods. 24 patients with mild to moderate hypertension were randomised into two treatment groups - nebivolol 5-10 mg per day vs nadolol 80-240 mgper day and treated for 6 months. Oral glucose tolerance test (OGTT) with the measurement of glucose and insulin levels: fasting, 30, 60, 90 and 120 minutes of test were performed initially and at the end of the study. Lipid profile and ambulatory blood pressure monitoring were also assessed for all patients.Results. Antihypertensive effect was comparable in both groups. At the same time, nebivolol improved parameters of OGTT and reduced insulin resistance, while in nadolol group these parameters remained unchanged. Lipid profile improved during nebivolol treatment and slightly worsened in nadolol group.Conclusion. Long-term nebivolol treatment can improve glucose tolerance and lipid spectrum in overweight patients, while administration of nadolol can slightly worsen lipid metabolism. These effects are unrelated to antihypertensive action of the drugs, which is comparable.